2011
DOI: 10.3109/17482968.2011.611139
|View full text |Cite
|
Sign up to set email alerts
|

A panel of macroautophagy markers in lymphomonocytes of patients with amyotrophic lateral sclerosis

Abstract: A potential role for macroautophagy dysfunction in the pathogenesis of amyotrophic lateral sclerosis (ALS) was hypothesized after the demonstration that selected markers are up-regulated in post mortem samples obtained from both patients and animal models of disease. We hypothesized that a putative dysfunction of this catabolic pathway could be operative also in peripheral blood mononuclear cells (PBMC) obtained from ALS patients, since these cells represent an accessible model for studying molecular pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is interesting to note that in Parkinson's disease (PD) and in amyotrophic lateral sclerosis (ALS), autophagy status in PBMCs was also studied. PBMCs from PD patients displayed a reduced expression of the chaperone-mediated autophagy carrier hsc70 protein [ 68 ] and results from PBMCs from ALS patients are contradictory: No significant difference of Beclin-1, LC3 immunoreactivity and mRNA Atg12 expression was observed between patients and controls although PBMC displayed a clear macroautophagy induction following exposure to rapamycin and lithium [ 69 ], while other data showed that the expression of the early autophagy-associated gene ATG12 was increased in PBMC from SCA7 patients in correlation with disease severity [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that in Parkinson's disease (PD) and in amyotrophic lateral sclerosis (ALS), autophagy status in PBMCs was also studied. PBMCs from PD patients displayed a reduced expression of the chaperone-mediated autophagy carrier hsc70 protein [ 68 ] and results from PBMCs from ALS patients are contradictory: No significant difference of Beclin-1, LC3 immunoreactivity and mRNA Atg12 expression was observed between patients and controls although PBMC displayed a clear macroautophagy induction following exposure to rapamycin and lithium [ 69 ], while other data showed that the expression of the early autophagy-associated gene ATG12 was increased in PBMC from SCA7 patients in correlation with disease severity [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) isolation was obtained by Ficoll-Histopaque density gradient centrifugation as described before [18]. PBMC pellets were then stocked at −80°C until assessment.…”
Section: Methodsmentioning
confidence: 99%
“…The pathology of ALS/FTD is typically accompanied by marked alterations in a key physiological process that is related to energy homeostasis: autophagy ( Sala et al, 2012 ). Since the deletion of autophagy-related genes is sufficient to cause neuronal death, autophagy is considered an essential homeostatic process for neurons ( Evans and Holzbaur, 2019 ).…”
Section: Defects Of Nutrient Signaling and Autophagy In Als/ftdmentioning
confidence: 99%